Prediction of pedicled flap survival preoperatively by operating indocyanine green angiography at 1,450 nm wavelength: an animal model study - Shi, Chenchen; Guo, Linxiumei; Song, Ruihu; Xu, Heng; Zhang, Yixin (Frontiers in Medicine, 2024)
Predicting flap viability benefits patients by reducing complications and guides flap design by reducing donor areas. Due to varying anatomy, obtaining individual vascular information preoperatively is fundamental for designing safe flaps. Although indocyanine green angiography (ICGA) is a conventional tool in intraoperative assessment and postoperative monitoring, it is rare in preoperative prediction. This study aimed to modify ICGA at 1,450 nm wavelength (ICG1450) and explore an approach to preoperatively predict the viability of pedicled skin flaps based on a mouse model. High-order branches of vessels were clearly visualized after ICG1450 so that the angiosomes division could be personalized, leading to a more accurate prediction of postoperative necrosis. In contrast to the conventional pattern, where 60% of the mice had necrotic areas beyond the predicted range, all of the necrotic areas predicted by our personalized design were at the distal end of the borderline. Further research could extend ICG1450 to humans in clinical practice for precision medicine. In conclusion, this study expanded the application potential of ICGA and validated the theory of angiosome.